2006
DOI: 10.1021/es052168w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Operating Parameters and Reactor Structure on Moderate Temperature Dry Desulfurization

Abstract: A moderate temperature dry desulfurization process at 600-800 degrees C was studied in a pilot-scale circulating fluidized bed flue gas desulfurization (CFB-FGD) experimental facility. The desulfurization efficiency was investigated for various operating parameters, such as bed temperature, CO2 concentration, and solids concentration. In addition, structural improvements in key parts of the CFB-FGD system, i.e., the cyclone separator and the distributor, were made to improve the desulfurization efficiency and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(60 citation statements)
references
References 12 publications
1
59
0
Order By: Relevance
“…In the optimum temperature window (700-800 o C) for dry-FGD process developed in our previous work [11], NO reduction performance is unknown. In this study, the potential of the sorbent-catalysts prepared from three low-cost materials including lime, fly ash, and the industrial waste material containing iron oxides, has been investigated for the simultaneous removal of SO 2 and NO at temperatures of 700-850 o C. NH 3 was chosen as the reducing agent for NO reduction.…”
Section: November 2007mentioning
confidence: 99%
See 2 more Smart Citations
“…In the optimum temperature window (700-800 o C) for dry-FGD process developed in our previous work [11], NO reduction performance is unknown. In this study, the potential of the sorbent-catalysts prepared from three low-cost materials including lime, fly ash, and the industrial waste material containing iron oxides, has been investigated for the simultaneous removal of SO 2 and NO at temperatures of 700-850 o C. NH 3 was chosen as the reducing agent for NO reduction.…”
Section: November 2007mentioning
confidence: 99%
“…The raw lime was ground and calcined in air at 450 o C for 3 h in order to convert Ca(OH) 2 to CaO. The sorbent-catalysts used in our experiments were prepared by specific procedures that were similar to the processes in our previous work [7,[9][10][11]. Two types of sorbent-catalysts were prepared, which are named as Sample-A and Sample-B hereinafter.…”
Section: Sorbent-catalysts Preparation and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…• C. [7] It is obvious that, simultaneous removal of SO 2 and NO x in the same temperature window in a single reactor will be more attractive from both the economic and equipment simplicity points of view than alternative techniques which remove SO 2 and NO x separately.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [8] have reported the experimental results from a pilot-scale circulating fluidized bed flue gas desulfurization (CFB-FGD) facility at a temperature range of 600-800 °C. They found that the desulfurization efficiency increased rapidly with increasing temperature above 600 °C.…”
mentioning
confidence: 99%